Formulasi Dan Uji Stabilitas Hair Tonic Kombinasi Ekstrak Daun Kelor (Moringa oleifera Lam.) Dan Madu Dengan Variasi Propilen Glikol - Oni Desmalia Putri; Ade Maria Ulfa; Gusti Ayu Rai Saputri (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Hair tonic is a beauty product to treat the scalp and hair that functions in strengthening, restoring and inhibiting hair loss. Moringa leaves contain flavonoid compounds as much as 27 μg/ml which function as antioxidants. Honey contains flavonoid compounds of pinocembrin group as much as 1.60 mg to 1.85 mg/100 g which function in overcoming hair loss. This study aims to formulate, evaluate and determine the stability of hair tonic preparations before and after storage containing moringa leaf extract and honey with variations of propylene glycol. The extraction of this study used the maceration method with 96% ethanol solvent and the stability test using the freeze thaw method. The yield of moringa leaves is 16.685%. Hair tonic is made into 3 variations of F1 (6%:6%:10%), F2 (6%:6%:15%), and F3 (6%:6%:20%). The results of organoleptic tests both before and after storage on formulations F1, F2, and F3 showed that all formulations had a solution shape, blackish-brown color and a distinctive aroma of moringa leaf extract. The results of the pH, homogeneity, specific weight, viscosity and irritation test before and after storage meet the requirements in accordance with SNI 19-4955-1998. Based on the stability test results, all preparations did not undergo significant changes in the pH test parameters, type weight and viscosity significance values >0.05. The results show that all preparations are stable during storage and do not irritate the skin.